Photonic crystal band edge coupled enhanced fluorescence from magneto-plasmonic cryosoret nano-assemblies for ultra-sensitive detection - Seemesh Bhaskar; Leyang Liu; Weinan Liu; Joseph Tibbs; Lucas D. Akin; Amanda Bacon; Brian T. Cunningham (APL Materials)
The fluorescence intensity associated with photon-emitters used as tags for the detection of molecular biomarkers for disease can be augmented by interfacing them with photonic crystal (PC) substrates. Although plasmonic nanomaterials are hybridized in such systems to facilitate better performance, the Ohmic losses associated with them still remain as a major bottleneck that limits the magnitude of achievable fluorescence enhancements. In this work, we present the design and synthesis of robust magneto-plasmonic, dielectric-metal, Fe3O4–Au cryosoret nano-assemblies for not only dequenching the quenched fluorescence signal but also for yielding directional steering emission output. The PC facilitates effective coupling of fluorescence emission to the PC band edge resonance and guided mode resonance by harnessing the transverse electric and transverse magnetic modes simultaneously. The resonance of the underlying PC is tailored to match the localized surface plasmon resonance of the magneto-plasmonic cryosorets (MCSs) and the emission of the radiating dipoles. The >450-fold PC band edge coupled enhancement achieved using the hottest hotspots from the MCSs in a cost-effective platform demonstrated ultra-sensitive (10 aM) sensing of a common chemical fluorophore used as a tag in biomolecular assays.